CORRUPTION CRIMES — STRENGTHENING THE RESPONSIBILITY OF OFFICIALS AND THE EFFECTIVENESS OF PUNISHMENT IN UZBEKISTAN (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a scientific-theoretical and practical analysis of the concept of corruption crimes in the criminal legislation of the Republic of Uzbekistan, the issues of their qualification, and the urgent need to strengthen the accountability of officials. The article reveals problems in the practice of sentencing for crimes such as bribery and abuse of official position, and develops well-founded proposals for amending the legislation to increase the effectiveness of punishment and improve the mechanisms for property confiscation.